Peningkatan Kemampuan Mengenal Angka Anak Usia 4–5 Tahun melalui Penerapan Media Number Maze Magnetic - Elsa Husnul Khotimah; Dadan Nugraha; Anggi Maulana Rizki (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Number recognition is a fundamental component of early numeracy development; however, previous studies indicate that early childhood learning is still largely dominated by worksheets and conventional instructional media, providing limited opportunities for concrete and interactive learning experiences. Existing studies have primarily employed conventional maze media, while magnetic-based learning media remain underexplored. This study aimed to improve the number recognition skills of children aged 4–5 years through the implementation of the Number Maze Magnetic, an instructional medium integrating maze games with magnetic manipulation activities. The study employed Classroom Action Research based on the Kemmis and McTaggart model involving two cycles with 15 children from Group A of TK Islam Amal Sholeh. Data were collected through observation, documentation, and field notes and analyzed using descriptive quantitative and qualitative techniques. The findings revealed a consistent improvement in children's number recognition skills, increasing from 44.16% in the pre-cycle to 65.62% in Cycle I and 87.50% in Cycle II. Beyond improving learning outcomes, the media also enhanced children's engagement, motivation, and active participation through meaningful hands-on learning experiences. The novelty of this study lies in the development of a magnetic maze learning medium that simultaneously integrates number recognition, number sequencing, and quantity-symbol matching into a single educational game. These findings imply that Number Maze Magnetic offers a practical and innovative instructional alternative for early childhood teachers to design interactive, child-centered numeracy learning activities that are easily implemented in classroom settings